The role of urban management in tourism development (Case study: Raamsar) - zohreh fani; ali mohammad nejhad (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2006)
The purpose of this study is examining the role of urban management in recogruzmg tourism potential, planning and exploitation of attractions. 011P<::tinnPr, were selected amonz tourists for understanding of the and recreational activities in Chabahar and Shiraz. We used the total monthly precipitation and average temperature, sunshine hours , wind speed, relative humidity, minimum relative humidity and maximum temperature data of Chabahar and Shiraz stations monthly and in a forty- year time span. Mieczkowski tourism climate index was used for this research. The results of this paper showed that climatic conditions of Chabahar in cold seasons of the year (i.e. Autumn and winter) are suitable for tourism activities but during the warm seasons of the year (i.e.spring and summer) face limitations. According to tourism climate index, January and February are the best time of the year for tourism activities in Chabahar. The best seasons for tourism in Shiraz are spring and Autumn and April, May and October has ideal condition for tourism.